2014
DOI: 10.1007/jhep10(2014)147
|View full text |Cite
|
Sign up to set email alerts
|

Notes on quantum entanglement of local operators

Masahiro Nozaki

Abstract: This is an expanded version of the short report arXiv:1401.0539, where we studied the time evolution of (Renyi) entanglement entropies for the excited state defined by acting a given local operator on the ground state. In the present paper, we introduce (Renyi) entanglement entropies of given local operators which are defined by late time values of excesses of (Renyi) entanglement entropies. They measure the degrees of freedom of local operators and characterize them in conformal field theories from the viewpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(149 citation statements)
references
References 88 publications
9
140
0
Order By: Relevance
“…Note that this instantaneous increasing of the entanglement entropy occurs because the interaction introduces the entanglement between the two scalar field theories homogeneously at the same time. This is in contrast with evolutions of entanglement entropy under quantum quenches [47,48] or local operator excitations [44][45][46], where the causal propagation of entangled pairs play an important role.…”
Section: Explicit Evaluations For Massless Interactionmentioning
confidence: 80%
See 1 more Smart Citation
“…Note that this instantaneous increasing of the entanglement entropy occurs because the interaction introduces the entanglement between the two scalar field theories homogeneously at the same time. This is in contrast with evolutions of entanglement entropy under quantum quenches [47,48] or local operator excitations [44][45][46], where the causal propagation of entangled pairs play an important role.…”
Section: Explicit Evaluations For Massless Interactionmentioning
confidence: 80%
“…This is naturally understood as in [44][45][46] because the state we are looking at is 25) in the original (unreplicated) theory and this is an maximally entangled state (EPR state).…”
Section: Jhep04(2014)185mentioning
confidence: 99%
“…There have also been some recent work discussing excited states in CFT's in various dimensions [11][12][13][14].…”
Section: Jhep01(2015)110mentioning
confidence: 99%
“…In the computation of the late time value (semi-inifinite interval) of the second Rényi entanglement entropy we use the (3.7). If we first take the limit of large central charge, the contribution to the second Rényi entropy becomes ∆S (2) 8 log 2t − 2 log c 2 (E.1) This is the logarithmic growth with time obtained in [6] (the negative part comes form the normalisation) and it should be possible to perform a similar computation for the entanglement entropy and match it with gravity using [34] as in [7]. On the other hand, as we saw in the text, if we know the answer for the full correlator (all quantum gravity effects taken into account) we can first take → 0 and obtain the entanglement constant.…”
Section: E Comments On Large C and Holographymentioning
confidence: 99%
“…In fact, at late times, the Rényi entanglement entropies saturate to constants that can be used to characterize local operators by the way they change quantum entanglement in a given state. Detailed reviews can be found in [6,7] and further results and applications to finite temperature and holography in [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%